SISTEM AUDITING DAN PENGENDALIAN INTERNAL TERHADAP PENINGKATAN BUDAYA KINERJA DINAS TENAGA KERJA SUMATERA UTARA (Lembaga Pengembangan Kinerja Dosen, 2022)
Unqualified Opinion on LKPD by the BPK RI 2021, which was obtained by the North Sumatra Provincial Government, partly due to the appropriateness of the effectiveness of internal control which also influenced the motivation of the Medan City Manpower Office, North Sumatra, to create a performance culture that is able to answer public needs through an audit system and internal control, although constrained in mastering the SIMDA application program. This study used the library research method and checklist tables as data analysis which were observed for 1 month. It was concluded that the results appear if the Medan City Manpower Office employees try to run the accounting system well, it can be seen from the routine evaluation and corrective action, preventive makes employees related to their fields continue to push themselves to improve their performance again, especially in understanding SIMDA. The performance culture that has been created can be seen from its social media accounts, which are very responsive and active in responding to the needs of the Medan people for jobs and the improvement of soft or hard skills utilizing training and coaching held by the Medan Manpower Office.